2021
DOI: 10.1051/0004-6361/202141157
|View full text |Cite
|
Sign up to set email alerts
|

ORion Alma New GEneration Survey (ORANGES)

Abstract: Context. The spectral energy distribution (SED) in the millimetre to centimetre range is an extremely useful tool for characterising the dust in protostellar envelopes as well as free-free emission from the protostar and outflow. Actually, the evolutionary status of solar-type protostars is often based on their SED in the near-infrared to millimetre range. In addition, the presence or absence of free-free emission can be considered an indicator of the source evolutionary stage (Class 0/I versus Class II/III). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 138 publications
(213 reference statements)
0
8
0
Order By: Relevance
“…The results of a previous single-dish study (Bouvier et al 2020) towards the same targets showed that the large scale (≤ 10 4 au) line emission is dominated by the Photo-Dissociation Region (PDR) or by the molecular cloud, rather than the protostellar envelopes. Interferometric observations are thus essential to detect hot corinos in this highly illuminated region.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The results of a previous single-dish study (Bouvier et al 2020) towards the same targets showed that the large scale (≤ 10 4 au) line emission is dominated by the Photo-Dissociation Region (PDR) or by the molecular cloud, rather than the protostellar envelopes. Interferometric observations are thus essential to detect hot corinos in this highly illuminated region.…”
Section: Introductionmentioning
confidence: 87%
“…They were initially 9 chosen protostellar sources based on single-dish studies (e.g. Chini et al 1997;Lis et al 1998;Nielbock et al 2003) satisfying the following three criteria: (1) detection in the (sub-)mm continuum emission; (2) estimated envelope mass ≤ 12 M ; (3) bona fide Class 0 and I protostars (see Bouvier et al 2020). The recent interferometric studies showed that most of these systems are in fact multiple systems (Tobin et al 2020;Bouvier et al 2021) which led to a total number of 19 studied targets.…”
Section: Introductionmentioning
confidence: 99%
“…As we do not know the dust temperature, T d , of the sources, we derived the dust optical depth for temperatures ranging between 100 and 500 K with steps of 10 K from 100 K to 200 K, and by steps of 20 K from 200 to 500 K, following the method described in Bouvier et al (2021). The observed 225 GHz flux provides a lower limit to T d .…”
Section: Dust Opacity Towards the Binary System Objects 11a And 11bmentioning
confidence: 99%
“…The errors are calculated using the error propagation method described in Appendix C.2. ofBouvier et al (2021), and include the calibration uncertainty of 15%(Alves et al 2019) and the source size uncertainty. The left and right panels refer to 11A and 11B, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation